Sustainable development: Learning the Quran using the Tartil Method - Syafril, Syafrimen; Erlina, Nova; Jaafar, Yaumas Azhar; Wekke, Ismail Suardi; Rahayu, Titik; Rashidi, Abbas; Hasan, Ahmad (2018)
This study aimed at investigating the effectiveness of learning the Quran using the tartil method. A quantitative approach (true experiment pretest-posttest control group design) was used as the research methodology. Sixty six (66) students whose Quran reading skills were poor were treated as the sample of this study. The data were collected through the Quran oral reading test and then analyzed through descriptive statistics using Statistical Package for Social Science (SPSS Windows 22.0). The results showed that learning the Quran using the tartil method was effective. Therefore, this method can be used as an alternative in learning the Quran.